Member (National Representative) - Yiatros, Stylianos (My University, 2026)
European Standardisation Body Technical Committee 350 : Sustainability of Construction Works to create sustainability standards for the construction sector. Also national representative for Sub-committee 1: Circular economy for the construction sector